Tinjauan Yuridis Penambahan Biaya Tambahan Pada Sistem Pembayaran Quick Response Code Indonesian Standard (QRIS) - Pramesti, Mutiara; Priyono, Ery Agus (Law, Development and Justice Review, 2026)
The 21st century marks a massive transition toward the digital era that changes the transaction behavior of society from cash to non-cash. One of the crucial innovations in Indonesia's payment ecosystem is the implementation of the Quick Response Code Indonesian Standard (QRIS). However, the implementation of QRIS has sparked controversy regarding regulatory disparities related to the imposition of additional administrative fees or surcharges on consumers, even though, according to regulations, the Merchant Discount Rate (MDR) fee is the responsibility of the business operators. This research aims to analyze the regulatory disparities arising from the implementation of QRIS and its impact on financial transactions in Indonesia. The research method used is normative juridical with a doctrinal approach that examines legislation and positive legal norms. The research results indicate a discrepancy between Bank Indonesia's regulation prohibiting additional charges to service users and the actual practice in the field where business operators set fixed rates to protect their profit margins. On the other hand, the use of QRIS significantly impacts the operational efficiency of banking, enhances financial inclusivity for MSMEs, and creates a cashless society ecosystem that supports transaction transparency